2021
DOI: 10.1155/2021/6622041
|View full text |Cite
|
Sign up to set email alerts
|

Information Fusion of Infrared Images and Vibration Signals for Coupling Fault Diagnosis of Rotating Machinery

Abstract: Rotating machinery has a complicated structure and interaction of multiple components, which usually results in coupling faults with complex dynamic characteristics. Fault diagnosis methods based on vibration signals have been widely used, however, these methods are intricate when identifying coupling faults, especially in the situation where coupling faults share similar patterns. As a noncontact and nonintrusive temperature-measuring technique, methods by infrared images can recognize multiple faults through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Wang_2021 [233] Rauber_2021 [219] Fan_2021 [234] Qian_2020 [235] Zhao_2020a [236] Chen_2020 [237] Li_2020 [238] Xin_2020 [239] Li_2019 [240] Hoang_2019 [241] Qian_2018 [242] Qian_2018 [242] Bai_2021b [243] Sharma_2021 * [25]…”
Section: Hidden Markov Modelsmentioning
confidence: 99%
“…Wang_2021 [233] Rauber_2021 [219] Fan_2021 [234] Qian_2020 [235] Zhao_2020a [236] Chen_2020 [237] Li_2020 [238] Xin_2020 [239] Li_2019 [240] Hoang_2019 [241] Qian_2018 [242] Qian_2018 [242] Bai_2021b [243] Sharma_2021 * [25]…”
Section: Hidden Markov Modelsmentioning
confidence: 99%
“…The frequency of vibration had been received from the ADC. These vibration signals were used to derive functions by extracting features (Bai et al, 2021). The accelerometer is connected to one end of the cable and to the other end to the DAQ system analog input and output (AIO) terminal.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Multi-source sensor information fusion for mechanical fault diagnosis is still in its infancy due to its complexity and feature extraction and fusion issues [24,25]. Due to the rapid development of deep learning-related research results, designing a complete fault diagnosis system based on multi-source information fusion using deep learning to realize the algorithm structure, including data preprocessing, classifiers, and evidence fusion, has become important [26,27]. Ghosh et al [28] discovered an evidence theory and multiinformation fusion to effectively-identified composite faults and provided maintenance instructions for composite fault diagnosis by fussing several maximal statistical distances and identifying fault classes technique.…”
Section: Introductionmentioning
confidence: 99%